Controlling attosecond pulse generation with a double optical gating - Chang, Zenghu (My University, 2007)
Numerical simulations have revealed that by adding a second harmonic field to a laser field with a time-dependent ellipticity, single isolated attosecond pulses can be generated as a result of the combined power of the two-color gating and the polarization gating. The duration of the pump laser applicable to this double optical gating scheme is a factor of 2 longer than that for the conventional polarization gating. Pulses with 200 attosecond duration can be generated from argon gas even with 10fs lasers. It was discovered that the number of attosecond pulses and their intensities could be controlled by either the relative phase between the two color fields or the carrier-envelope phase.